Analysis of air jets velocity attenuation at special initial conditions - Orest Voznyak; Nadiia Spodyniuk; Olena Savchenko; Oleksandr Dovbush; Mariana Kasynets; Oleksandra Datsko (Diagnostyka, 2022)
The article is devoted to solving the significant problem of efficiency increasing of air distribution in the premise by swirl air jet. The aim of the article is to decrease coefficient of velocity attenuation due to intensification of initial turbulence of different air streams leakage from the air distributor and to obtain of analytical equations for calculation of air distribution in a room to ensure the normative indoor air parameters. Effect of flow twisting results in a reduction of the velocity attenuation coefficient by 2.4 times. The regression analysis testified that the attenuation coefficient of the swirl air jet is more affected by the angle of the twisting plates inclination and less affected by the angle of change of the air flow direction. The attenuation coefficient of all types of rectangular air jets is more influenced by the the ratio of the sides of slit b/l and the angle of change of the air flow direction is also less affected. To minimize the attenuation factor, it is effective to use air distributors at smaller swivel plates inclination angles for swirl air jets and a smaller slit size ratio for all types of rectangular air jets.